Analisa Aliran Daya pada Penyulang Sei Keruh di PT. PLN (PERSERO) UIWS2JB UP3 Jambi ULP Kuala Tungkal Menggunakan Software ETAP 12.6 - Arti, Zahwa Berliana; Suprapto, Eko; Thamrin, NJ. (Universitas Batanghari Jambi, 2024)
In electric power systems, power flow studies are conducted to gather data on power flow. Including active and reactive power, voltage on each bus, voltage magnitude and phase angle, active and reactive power flowing through each channel, and the state of every piece of equipment to ascertain whether it satisfies the necessary standards for distributing the necessary electrical power. In this research, ETAP software is used to simplify and speed up the power flow calculation process. According to the analysis's findings, the higher the transformer load percentage, the smaller the voltage. The smallest voltage at point JE383 – JE507 which is located at the end of the line is 19,719 kV with an assumed load of 95%. The greater the transformer load percentage, the greater the current. The largest current is located at the base, namely at the PLTMG – JEX109 point of 49.2 A with an assumed load of 95%.